Effects of Strongbacks and Strappings on Vibrations of Timber Truss Joist Floors - Shuo Xue; Zhanyi Zhang; Zhanyi Zhang; Haibin Zhou; Yinlan Shen (Shock and Vibration)
It is well known that the vertical vibrations of lightweight timber floors would cause discomfort to the occupants. As a new kind of flooring system, the metal-plate-connected timber truss joist floors were developed due to their larger spans and easier crossing of pipes and cables after sawn timber and I-joist floors. In this paper, the vibration modes and transfer functions of sixteen metal-plate-connected timber truss joist floors over a nominal span of 6 m were determined experimentally to measure the changes in vibration frequencies and transmissions obtained after the installation of strongbacks and strappings. The results showed that the fundamental natural frequencies of the metal-plate-connected timber truss joist floors at a 400 mm joist spacing were about 15 Hz, while the frequencies of the floors at a 600 mm joist spacing were about 12.5 Hz. The bracing elements of the strongbacks and strappings mainly enhanced the system stiffness in the across-joist direction of the flooring system, but they did not govern the fundamental natural frequencies of the floors and just changed the spacing of adjacent natural frequencies. The bracing elements as secondary elements of the floors also altered the vibration transmission paths in the across-joist direction. The frequencies where the stronger vibration transfers happened in the direction perpendicular to floor joists were generally above 15 Hz. Proper installation measurements of bracing elements in practical control need to be taken to alleviate the vibration response intensity at the targeted locations and frequencies.